Should Islamic Window be converted into a Full-Fledge Islamic Bank? A case study in Indonesia - Anggito Abimanyu; Abdullah At Tamimi (Faculty of Economic and Business, 2024)
Research Originality: This research provides fresh perspectives on the future landscape of Islamic banking, particularly concerning the Islamic window. The paper stands out for its originality as it undertakes an empirical study utilizing a mixed method. This study is also expected to answer the research gap between literature studies, empirical studies, and implemented policies. Additionally, it is driven by the objective of contributing to the existing literature on Islamic finance.Research Objectives: This study dives into whether converting Islamic Business Units (UUS) into full-fledged Islamic Banks (BUS) leads to performance enhancement.Research Methods: There are two types of data analysis methods, namely qualitative and quantitative. The qualitative analysis method comes from a collection of literature reviews and institutional opinions from Islamic banking experts in the world. This study employs a multi-pronged quantitative approach to investigate the performance and consumer perception of Islamic banking services with an emphasis on UUS and BUS.Empirical Result: The results indicate that UUS and BUS structures adhere to Sharia principles and achieve commendable performance. However, analysis of financial reports across many countries, including Indonesia, shows that UUS's financial performance is generally better than BUS. The research further emphasizes that internal factors like capital adequacy, asset quality, and management capabilities, rather than the institutional structure itself, hold greater sway in driving performance improvement. Forced conversion of UUS could even hinder overall progress. Implications: Beyond financial considerations, the study explores consumer behavior through surveys with educated individuals. The results indicate that their choice between BUS and UUS products is guided by practical factors such as financial returns, costs, and service reliability offered by each structure. JEL Classification: G21, G28 How to Cite:Abimanyu, A., & At Tamimi, R. A. (2024). Should Islamic Window be Converted into a Full-Fledge Islamic Bank? A Case Study in Indonesia. Etikonomi, 23(1), 183 – 200. https://doi.org/10.15408/etk.v23i1.35082.